How did farmers act? Ex-post validation of linear and positive mathematical programming approaches for farmlevel models implemented in an agent-based agricultural sector model - Gabriele Mack; Ali Ferjani; Anke Möhring; Albert von Ow; Stefan Mann (Bio-based and Applied Economics (BAE), 2019)
This study evaluates linear programming (LP) and positive mathematical programming (PMP) approaches for 3,400 farm-level models implemented in the SWISSland agent-based agricultural sector model. To overcome limitations of PMP regarding the modelling of investment decisions, we further investigated whether the forecasting performance of farm-level models could be improved by applying LP to animal production activities only, where investment in new sectors plays a major role, while applying PMP to crop production activities. The database used is the Swiss Farm Accountancy Data Network. Ex-post evaluation was performed for the period from 2005 to 2012, with the 2003-2005 three-year average as a base year. We found that PMP applied to crop production activities improves the forecasting performance of farm-level models compared to LP. Combining PMP for crop production activities with LP for modelling investment decisions in new livestock sectors improves the forecasting performance compared to PMP for both crop and animal production activities, especially in the medium and long term. For short-term forecasts, PMP for all production activities and PMP combined with LP for animal production activities produce similar results.
Keywords: C61; Q18; Q19; 330; Agent-based sector model; farm-level model; linear programming; positive mathematical programming; ex-post validation